The Role of Digital Video Content in Building Perception and Trust in Islamic Educational Institutions - Muthi'ah Rahman; Annisa Tri Ananda Dewi; Ahmad Rausyan Fikri; Maulidatul Adzimah; Abdul Aziz Alwahedi; Moh Mohlas; Faizin Faizin (Education and Sociedad Journal, 2025)
This study aims to analyze the role of digital video content in building positive perceptions and increasing public trust in Islamic educational institutions. The focus of the study includes the function of digital video as a medium for shaping the institution's image, its influence on the trust of parents and prospective students, and effective content presentation strategies in attracting public attention. The study used a qualitative method with a case study approach. The most appropriate data collection techniques were in-depth interviews, observation of the institution's digital video content, and social media documentation, as they were able to explore public perceptions, experiences, and responses more comprehensively. The results showed that digital video content that showcases real-life activities, Islamic values, achievements, and testimonials can shape positive public perceptions of Islamic educational institutions. Furthermore, a creative, informative, and consistent video presentation has been shown to increase public trust and strengthen the institution's image. The implications of this study indicate that strategic use of digital media can be an effective tool in educational marketing and strengthening institutional relationships with the community.